2003
DOI: 10.1046/j.1344-3941.2003.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between plasma leptin concentrations and the distribution of body fat in crossbred steers

Abstract: The objective of the present study was to examine the relationship between plasma leptin levels and fat distribution in crossbred steers. Twenty‐four crossbred steers (Japanese Black × Holstein) were used in this study. Six steers belonged to the growing phase (11 months of age), and 18 steers to the finishing phase (from 21 to 28 months of age). Plasma leptin levels correlated positively with body fat weight (r = 0.807, P < 0.01), body fat percentage (r = 0.802, P < 0.01), visceral fat weight (r = 0.807, P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The fact that both clones had consistently higher amounts of mesentery fat and fatty acids compared with the comparators is hardly surprising because these two clones are genetic copies of a top breeding bull and they both exhibited the most preferable values as expected (19,20). The other four parameters found different between clones and comparators: yield score, the proportion of longissimus thoracis muscle to body weight, the muscle moisture, and the amount of crude protein in the semitendinosus muscle, all fall within the normal range of the previously recorded industry standards (19,21,22). Therefore, none of these parameters are of public concern.…”
Section: Discussionsupporting
confidence: 74%
“…The fact that both clones had consistently higher amounts of mesentery fat and fatty acids compared with the comparators is hardly surprising because these two clones are genetic copies of a top breeding bull and they both exhibited the most preferable values as expected (19,20). The other four parameters found different between clones and comparators: yield score, the proportion of longissimus thoracis muscle to body weight, the muscle moisture, and the amount of crude protein in the semitendinosus muscle, all fall within the normal range of the previously recorded industry standards (19,21,22). Therefore, none of these parameters are of public concern.…”
Section: Discussionsupporting
confidence: 74%
“…Minton et al (1998), Geary et al (2003 and McFadin et al (2003) reported very different relationships between blood leptin level and fat in separate fat depots in cattle with visceral fat more strongly correlated than s.c. fat depth. But there are contrary data: Yamada et al (2003) found fat location did not affect associations between plasma leptin level and fat mass in Japanese Black 3 Holstein steers in the growing or fattening phases (11 to 28 months) despite their propensity for i.m. fat deposition (Zembayashi et al, 1995).…”
Section: The Biological Significance Of Leptin In Animalsmentioning
confidence: 87%
“…fat. Yamada et al (2003) compared relationships between leptin and carcase quality in Japanese Black 3 Holstein steers at 11 months and 21 to 28 months. Using pooled data, leptin level correlated strongly with body fat (r 5 0.802) but less strongly when data for young and older steers were treated separately.…”
Section: The Biological Significance Of Leptin In Animalsmentioning
confidence: 99%
“…Ghrelin displays a wide spectrum of biological functions such as the regulation of appetite and food intake, gastrointestinal motility, gastric acid secretion, endocrine and exocrine pancreatic secretions, cell proliferation, glucose and lipid metabolism, and cardiovascular and immunologic processes (De Vriese et al 2008, Soares et al 2008. Leptin acts to regulate food intake, energy expenditure, homeostasic body weight, and consequently to influence fat deposition in both animals and humans (Yamada et al 2003). Thyroid hormones modulate energy metabolism (Huszenicza et al 2002), in which carbohydrates and lipids are the major constituents.…”
Section: Introductionmentioning
confidence: 99%